Kualitas Sumber Daya Manusia dan Strategi Bisnis Perusahaan Perusahaan Logistik Nasional - Kurniawan, Arif; Nofrisel, Nofrisel; Widodo, Erna; Tatiana, Yana; Perwitasari, Erni Pratiwi (Institut Transportasi dan Logistik Trisakti, 2023)
The purpose of the study is to find out the direct and indirect contribution of human resources quality to the achievement of revenue target mediated by business strategy of the national logistics company. This research used SmartPLS 3.0-SEM and the sample was 53 employees of the Angkasa Pura Logistik head office. The result of the research indicates that the corporate business strategy is able to mediate human resources quality to the revenue target achievement in Angkasa Pura Logistik. The company provides its employees with education and trainings to improve their quality. During the pandemic, the company had implemented the newest business strategy by opening new branches with better operation. The company should also choose the employees selectively with competences needed in the respective fields. Angkasa Pura Logistik sustainably has improved and enhanced its service and product in line with the increasing demand. For further research, it can be proposed to study the contribution of these variables on similar companies in other countries.